Linguistic creativity in restaurant naming in Manado: Between local identity and global influence - Vivi Nansy Tumuju; James Edward Lalira (Universitas Dian Nuswantoro, 2025)
This study aims to explore linguistic creativity in restaurant naming in Manado, Indonesia, and how restaurant names reflect local identity, global influences, and commercial branding strategies. The study was conducted using a descriptive mixed-methods design, which involved analyzing 230 restaurant names across five districts of Manado: Malalayang, Sario, Mapanget, Tuminting, and Wenang. Data were analyzed using descriptive frequency analysis and qualitative linguistic interpretation, aided by semi-structured interviews with 20 restaurant owners or managers. The results indicate that the linguistic elements used in restaurant names are Indonesian, local, foreign, and hybrid, and are used strategically. Indonesian elements offer familiarity and wide accessibility, local terms offer cultural authenticity, and foreign and hybrid forms create modern, global, and differentiated brand images. Linguistic creativity is manifested in the form of metaphor, abbreviation, phonological appeal, lexical innovation, and culturally marked terms like “Rumah Makan,” “Warung,” and “Kios.” This study contributes to the field of linguistic landscape and commercial naming studies by demonstrating that restaurant names are not merely business labels but semiotic resources used to negotiate local identity, global aspiration, and market positioning.